IMPLEMENTASI UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI WILAYAH HUKUM KABUPATEN SEMARANG - Dimas Surya Guritno,; Arikha Saputra, (The Juris, 2022)
Every motorized vehicle that is operated and/or used on the highway must meet all technical requirements and roadworthiness requirements as stipulated by Law No. 22 of 2009 concerning Road Traffic and Transportation. The objectives of this study are to: 1) examine more deeply the implementation of Law No. 22 of 2009 concerning Road Traffic and Transportation on roadworthiness tests for public transportation vehicles in the jurisdiction of Semarang Regency, 2) Knowing the obstacles related to Implementation of Law No.22 of 2009 concerning Road Traffic and Transportation on roadworthiness tests in the jurisdiction of Semarang Regency. This type of research is field research and uses a normative juridical approach in obtaining data, where a normative juridical approach is carried out based on the main legal material by examining the concepts, principles, and legal theories as well as legislation related to the Act. Law No.22 of 2009 concerning Road Traffic and Transportation in the jurisdiction of Semarang Regency. The results of this study obtained a conclusion that: The implementation of Law No. 22 of 2009 concerning Road Traffic and Transportation on roadworthiness tests for public transport vehicles is in accordance with the provisions contained in Article 54 paragraph (3) regarding KIR testing of public transport vehicles. in the jurisdiction of Semarang Regency too has been implemented using a smart card where the implementation of a smart card is a substitute for a test book which is a policy of the Central Government through the Ministry of Land Transportation program.